BUDIDAYA BEBERAPA VARIETAS IKAN SEPAT RAWA (Trichogaster trichopterus Pall) DENGAN PEMBERIAN PAKAN KOMERSIAL - Akhmad Murjani (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2019)
The purpose of this study was to determine the speed of growth and survival of several varieties of three spot goramy (Trichogaster trichopterus Pall) from themonotonous marshes, tidal marshes, bogs and swamps rainfed fields that are kept inhapa Galam.Three spot goramy (Trichogaster trichopterus Pall) are able to live and adapt in the cultivation environment, and can be fed with artificial feed like most culture fish.Variations in the type of fishes did not significantly affect marsh growth and survivalof fish that are kept in swamp ride cultivation environment. The mean relative growthrate of weight it is best to treatment C (fish from the marsh three spot goramy rainfed) of 29.36%. Average growth rate is relatively long it is best to treatment B (three spotgoramy of marsh meadow Galam) for 9.35 %. Conversion is best to feed on the Ctreatment (fish from the marsh three spot goramy rainfed) of 6.80. the best survivalwas in treatment B, C, D of 75.56%.